An experimental study on efficacy of Kalium phosphoricum 6x, 30c and 1m potencies on germination of vigna radiata using quantitative and qualitative assessment of germination parameters - Ramchandra, Shirurkar Manali; Paul, Sherlyn E (Indian Journal of Integrative Medicine, 2023)
This article presents an experimental study conducted to investigate the efficacy of different potencies of Kalium Phosphoricum on the germination and growth of Vigna Radiata (Green gram) seeds. The study aimed to determine the impact of Kalium Phosphoricum on seed germination, compare the growth differences among different potencies, and identify the most effective potency for plant development. The methodology involved soaking the seeds in various potencies, followed by the cotton pad germination method. The germination parameters were assessed quantitatively by calculating the percentage of germination, and qualitatively by measuring shoot and root lengths. The results demonstrated that Kalium Phosphoricum potencies had a significant effect on seed germination and growth, with the most effective potency observed to be 6X.